Analysis of different evaluation indexes for prostate stereotactic body radiation therapy plans: conformity index, homogeneity index and gradient index. Issue Volume 3:Issues 3(2019) (12th September 2019) - Cao, Tingting; Dai, Zhitao; Ding, Zhen; Li, Wuzhou; Quan, Hong
Abstract: Objective: This study analyzed different definitions of the conformity index (CI), homogeneity index (HI), and gradient index (GI) used in evaluation of prostate cancer stereotactic body radiation therapy. Methods: A total of 10 patients with localized prostate cancer staged T1–T2a were selected randomly, from which two stereotactic body radiation therapy plans were designed with CyberKnife and EDGE systems for each patient based on the same images and contours. CI, HI, and GI with different definitions were calculated based on a dose‐volume histogram of treatment plans. Results: For four definitions of CI, the results showed that the values calculated by the Radiation Therapy Oncology Group, Lomax and Scheib, and Van't Riet were closer to 1 for EDGE plans, except for that by the Saint‐Anne, Lariboisiere, and Tenon group. Meanwhile, CI values of Van't Riet et al were lower than other definitions, which showed high accuracy to describe the conformity between the target volume and prescribed isodose line. For five definitions of HI, CyberKnife plans showed lower values than EDGE plans. HI calculated based on the D2 ( D5 ) and D98 ( D95 ) were lower than that calculated by the Dmax to Dmin, whereas the standard deviation was higher than others. For the dose GI, the results of effective radius and modified GI showed that EDGE plans had a steeper dose fall‐off, which is inverse to the conventional GI. Conclusions: These indexes can all be objective tools for the evaluation of plan quality. Our results showed better conformity of dose distribution and dose gradient for EDGE plans, but better uniformity for CyberKnife plans. The conformation number and S‐index were recommended to accurately describe the conformity and uniformity of dose distribution. The ∆Riso and modified GI were also recommended to calculate the dose gradient.